Respuesta :
well hmmm
let's say
b = amount of buzz cuts
f = amount of flat-top cuts
now, the total price for all the buzz cuts, since each one is $9, will then be 9*b or 9b
and the price for all flat-top cuts, since each is $13, will then be 13*f or 13f
one day Jerry made a total of $600, so we know, whatever "b" and "f" are, we know their price sum was 600,
thus 9b + 13f = 600
now, Jerry "knows that he cut three times as many buzzes as flat-tops", so, whatever "f" is, "b" is three times that much, or 3*f, so b = 3f
now then [tex]\bf \begin{cases} 9b+13f=600\\ \boxed{b}=3f\\ ----------\\ 9\left( \boxed{3f} \right)+13f=600 \end{cases}[/tex]
solve for "f"
let's say
b = amount of buzz cuts
f = amount of flat-top cuts
now, the total price for all the buzz cuts, since each one is $9, will then be 9*b or 9b
and the price for all flat-top cuts, since each is $13, will then be 13*f or 13f
one day Jerry made a total of $600, so we know, whatever "b" and "f" are, we know their price sum was 600,
thus 9b + 13f = 600
now, Jerry "knows that he cut three times as many buzzes as flat-tops", so, whatever "f" is, "b" is three times that much, or 3*f, so b = 3f
now then [tex]\bf \begin{cases} 9b+13f=600\\ \boxed{b}=3f\\ ----------\\ 9\left( \boxed{3f} \right)+13f=600 \end{cases}[/tex]
solve for "f"
Let x=the number of Buzz & let y = number of flat:
9x+13y = 600
But 3x = y (given) then ==> 9x+(13)3x= 600==48x =600 x = 12.5
& y=37.5 (PROOF 9 x 12.5) + (13 x 37.5) =600
9x+13y = 600
But 3x = y (given) then ==> 9x+(13)3x= 600==48x =600 x = 12.5
& y=37.5 (PROOF 9 x 12.5) + (13 x 37.5) =600